2020
DOI: 10.1016/j.combustflame.2020.01.041
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of hydrogen–oxygen–argon cellular detonations with a constant mean lateral strain rate

Abstract: The present work revisits the problem of modelling the real gaseous detonation dynamics at the macro-scale by simple steady one-dimensional (1D) models. Experiments of detonations propagating in channels with exponentially expanding cross-sections (exponential horns) were conducted in the H 2 /O 2 /Ar reactive system. Steady detonation waves were obtained at the macroscale, with cellular structures characterized by reactive transverse waves. For all the mixtures studied, the dependence of the mean detonation s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
3
4
0
Order By: Relevance
“…From the instantaneous flow fields, these regions were seen to be thin non-reactive tails in the gas between the leading shock front and the transverse waves due to the lower temperature, which were reported numerically by Gamezo et al. (2000) and observed experimentally by Xiao & Radulescu (2020) in a hydrogen–oxygen–argon mixture.
Figure 15.The 2-D flow fields of the projected Lagrangian values in the position where the Lagrangian particles experienced the maximum thermicity in 2–7Ar mixture.
…”
Section: Resultssupporting
confidence: 66%
See 1 more Smart Citation
“…From the instantaneous flow fields, these regions were seen to be thin non-reactive tails in the gas between the leading shock front and the transverse waves due to the lower temperature, which were reported numerically by Gamezo et al. (2000) and observed experimentally by Xiao & Radulescu (2020) in a hydrogen–oxygen–argon mixture.
Figure 15.The 2-D flow fields of the projected Lagrangian values in the position where the Lagrangian particles experienced the maximum thermicity in 2–7Ar mixture.
…”
Section: Resultssupporting
confidence: 66%
“…There are regions in the cellular structure where the Lagrangian particles did not complete the induction process (figures 15, 16). From the instantaneous flow fields, these regions were seen to be thin non-reactive tails in the gas between the leading shock front and the transverse waves due to the lower temperature, which were reported numerically by Gamezo et al (2000) and observed experimentally by Xiao & Radulescu (2020) in a hydrogen-oxygen-argon mixture.…”
Section: Dispersion In Induction Time Scalesupporting
confidence: 58%
“…The present study addresses whether a curvature based prediction of critical transmission is compatible with experiments in weakly unstable detonations and can quantitatively predict the critical diffraction conditions. of such weakly unstable cellular hydrogen detonations at low pressure, which are characterized by much longer reaction zones as compared to induction zones, can be well captured by the predictions of the ZND model with curvature 23 and neglect of the cellular structure. It is thus of interest to verify whether the diffraction process in these same mixtures can be equally well predicted by neglecting the influence of the cellular structure for these conditions using a critical curvature criterion, as suggested by Lee 22 .…”
Section: Introductionmentioning
confidence: 79%
“…This resolution of 7 µm corresponds to 40 to 90 grid points in the induction length (depending on pressure), which is well above usual recommendations. Given that low pressure hydrogen detonations have reaction zones longer than the induction zones by an order of magnitude, and halfreaction zone lengths 2-3 times larger than the induction zone length 23 , our effective resolution is on the order of 100 to 200 grid points per half reaction length. For reference, the recently reported state of the art simulations of Shi, Uy, and Wen 10 used only 24 grid points per half reaction length, a limitation imposed by the lack of AMR.…”
Section: Numerics and Experimentsmentioning
confidence: 99%
See 1 more Smart Citation